weighted blankets, sensory-based interventions, autism spectrum disorder - Teresa A. May-Benson; Sarah Schoen; Alison Teasdale; Jane Koomar (Scholarworks @ WMU, 2021)
Background: Goal Attainment Scaling (GAS) is advocated as a meaningful outcome measure for parents and clinicians using an Ayres Sensory Integration® Intervention (ASI) approach. Although used in several treatment effectiveness studies, reliability of therapist goal writing and scoring has not been established in this area. Method: Ten occupational therapists and 40 parents of children receiving ASI participated across two clinical sites. The interview therapists and inter-rater therapists wrote GAS goals based on the same goal-setting interviews conducted with parents. Follow-up parent interviews were conducted post-ASI intervention, and the GAS goals were rated by both the interview therapists and inter-rater therapists. Results: Seventy-eight percent of interview therapist and inter-rater therapist-written goals agreed on content. Intra Class Correlation coefficient of agreement between the two sets of raters was .70 for the total score. Control of bias for establishing and rating the projected level of performance and scaled GAS goals was within an acceptable range. Conclusion: Findings contribute reliability evidence for use of GAS with children with sensory processing and integration challenges. Two therapists, from different clinical sites who were unfamiliar with the child, identified goal areas, wrote similar GAS goals based on the same parent interview, and scored goals post intervention with good inter-rater reliability.